Non-EFL Students' Ability and Their Difficulties in Reading Comprehension Test - Nur Fitria, Tira (STIT Buntet Pesantren Cirebon, 2023)
This research describes the non-EFL students’ ability and their difficulties in reading comprehension tests. This research is descriptive qualitative research. The analysis from Google Form response shows that the student’s average is 20.15 from 50 points, the students’ median is 18 from 50 points (correct answer) and the students’ range is between 9 (lowest score) reading texts up to 40 (highest score). The students’ problems in the reading test are about a number of questions, limited time in doing the test, unfamiliar and uninteresting topics of reading text, number of texts, number of paragraphs in the text, varied types of text-related questions, unfamiliar vocabularies, difficulty in understanding the meaning of the question and the content of the text, and difficulty in answering types of reading comprehension such as the main idea, reference, stated detail, unstated detail, vocabulary, conclusion/inference, etc. Both English teachers/lecturers and students must collaborate to answer these problems. English teachers/lecturers can evaluate the students’ reading levels effectively, explain the reading method clearly, and implement an exciting strategy in teaching reading to stimulate the students to read texts. While students need to read regularly, choosing reading according to interest, reading various topics, and combining different methods in reading English.